Imagery in Poetry: An Assessment of Poems in Compulsory English Course of Class Twelve in Nepal - Paudel, Yograj (Kalika Journal of Multidisciplinary Studies, 2021)
Poetic feeling and emotions are mostly expressed through imagery. This study analyzes poetic imagery in the prescribed poems in the compulsory English course of class twelve in Nepal. Based on primary and secondary data, this paper first deductively generalizes definition of imagery and its types. Then it makes analysis of imagery in all prescribed poems. It is found that most common images are visual, auditory, tactile and kinesthetic. Olfactory and gustatory images are less realized in the poems. Most dominant imagery in the poems is visual. Most of the poets have used visual imagery to contextualize and communicate desired message effectively so as to make their readers perceive their feelings well.